Implicit-Euler Implementation of Super-Twisting Observer and Twisting Controller for Second-Order Systems - Xiong X.; Kikuuwe R.; Kamal S.; Jin S. (My University, 2025)
This brief proposes new discrete-Time algorithms of the super-Twisting observer and the twisting controller to be applied to second-order systems. The algorithms are based on the full implicit-Euler discretization, which contributes to the elimination of chattering. Proofs of some stability properties of the discretized twisting controller are also provided. Simulations show that, as compared to traditional explicit-Euler schemes, the proposed scheme avoids the chattering both in trajectory tracking output and control input in the presence of external disturbances. © 2004-2012 IEEE.